Effect of Nape Acupuncture Combined with Swallowing Training on Dysphagia in Patients with Parkinson's Disease - Linjing WANG; Xue WANG; Jiyao ZHANG; Jiashuai LI; Xinlei HOU; Luwen ZHU (康复学报, 2020)
Objective:To explore the effect of acupuncture combined with swallowing training in patients with Parkinson's disease with swallowing dysfunction.Methods:From August 2017 to August 2019, a total of 120 patients with Parkinson's dysphagia with gradesⅡtoⅣof the"Kubota Water Swallowing Test"were selected and randomly divided into treatment group (n=60) and control group (n=60). The control group was treated with swallowing training, and the treatment group was treated with nape acupuncture combined with swallowing training,30 min each time,6 times a week for 4 weeks. Standardized Swallowing Assessment (SSA), Videofluoroscopic Swallowing Study (VFSS) were used to evaluate swallowing, and Swallowing-related Quality of Life (SWAL-QOL) was used to evaluate quality of life before and after 4 weeks'treatment.Results:There was no significant difference in the SSA, VFSS and SWAL-QOL scores before treatment between the two groups (P>0.05). After 4 weeks'treatment, the SSA scores of the two groups were lower than those before treatment, and the VFSS and SWAL-QOL scores were all higher than those before treatment (P<0.05). At end of treatment, the SSA scores of the treatment group were (21.67±3.34), which were lower than those of the control group (25.16±3.82), and the difference was statistically significant (P<0.05). The VFSS and SWAL-QOL scores were (7.68±1.03) and (137.24±12.97), which were all higher than those of the control group (5.94±1.72) and (121.98±9.32), and the differences were statistically significant (P<0.05).Conclusion:Npae acupuncture combined with swallowing training can effectively improve the swallowing function and quality of life of patients with Parkinson's dysphagia, which were better than the single swallowing training.